CALCAREOUS NANNOFOSSIL DISTRIBUTION IN PELAGIC RHYTHMIC SEDIMENTS (APTIAN-ALBIAN PIOBBICO CORE, CENTRAL ITALY) (Rivista italiana di Paleontologia e Stratigrafia, 1991)
The Aptian-Albian Scisti a Fucoidi Formation from Central Italy represents a spectacular example of pelagic cyclic sedimentation. It consists of a varicolored sequence of marlstone, marly claystone, and marly limestone, with subordinate limestone. Several black shale layers are scattered throughout the formation. In order to clarify the mechanisms responsible for the rhythmicity, the Scisti a Fucoidi Formation was multidisciplinarly investigated in detail in the Piobbico core (Marche, Central Italy). Calcareous nannofossil assemblages were quantitatively analyzed, in three segments of the core in order to discern paleoceanographic fluctuations. These intervals were selected as representative lithologic end members characterized by three different types of cyclicity. On the basis of nannofossil assemblages, the following indices were identified: a Diagenesis Index (dissolution and overgrowth during burial), a Primary Dissolution Index (dissolution mainly at the sediment/water interface), Paleoecological Indices of higher and moderate fertility, of carbonate productivity, and of warmer and cooler waters. Within the Scisti a Fucoidi, the Upper Aptian, consisting of red lithotypes with interbedded green layers, is strongly affected by diagenesis. However, nannoconids still record fluctuations of carbonate productivity probably in a cooler more oxygenated paleoenvironment. Lowermost Albian maroon claystones with frequent interbedded black shales, are affected by extremely sever dissolution but a few episodes of increased carbonate productivity are recorded by changes in nannoconid abundance. Upper Albian greenish-gray marly limestones with cyclically modulated black shales, record slight rhythmic fluctualions in surface water fertility. Correlations between the distribution of nannofossil indices and lithology along with foraminifer and trace fossil patterns point to a response to orbital perturbations capable of triggering changes in ocean circulation, chemistry, and ecology. The rhythmic black shales of this interval probably accumulated because of an increase in stratification or decrease in oxygenation related to weaker temperature gradients and warmer waters, respectively.